Developing young learners' reading competence in Ethiopia: A critical review of the Ministry of Education's guidelines for developing supplementary reading materials - Samuel Belayneh Kame; Mulugeta Tarekegne Tsegaye; Mona Evelyn Flognfeldt; Margareth Sandvik (College of education, Bahir Dar University, 2024)
This study presents a critical review of the official guidelines established in 2016 by the Ethiopian Ministry of Education offering detailed criteria for the development and selection of supplementary reading materials (SRMs) for primary school learners to enhance their reading competence. Despite interventions during the last couple of decades to enhance reading performance in Ethiopia, sufficient improvement has not been seen. The study examined the extent to which the Ministry's guidelines are conducive to appropriate development of students' reading fluency and reading comprehension with a focus on Grades 1-4. We analyzed the criteria in view of current research in the science of reading, building also on theories of multimodality and text linguistics. Findings show that the SRM selection and development guidelines align with a traditional simple view of reading (SVR). We argue that developing and selecting SRMs based on an active view of reading, highlighting a learner-sensitive affective dimension of learning, has the potential to make SRMs more motivating and thus more conducive to young learners' reading development. With this perspective on the SRM guidelines, the article ends with a reflection on the potential pedagogical implications of these new insights as part of reading teachers' professional knowledge base.